(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the demographic, cultural, social and political aspects of the development of the population of the Turkestan region in the XVIII – early XX century. The article analyzes the ethnocultural interaction of sedentary and nomadic populations, the impact of migration processes and the colonial policy of the Russian Empire on economic and social institutions. Special attention is paid to the traditional forms of organization of urban and rural settlements, the role of mahallas, as well as ethnosocial groups such as Tore, Kozha, Tolengut and Shalakazakh. The study of the ethnic structure of the region makes it possible to identify patterns of transformation of social relations, as well as the impact of political and economic changes on the formation of Kazakh identity